Executive Editor's Note Vol.6(1) - Alam, Mahmudul (Journal of Business and Technology (Dhaka), 2012)
DOI: http://dx.doi.org/10.3329/jbt.v6i1.9990 Journal of Technology (Dhaka) Vol. 6(1), January-June, 2011